2014
DOI: 10.5888/pcd11.140017
|View full text |Cite
|
Sign up to set email alerts
|

Institution-to-Institution Mentoring to Build Capacity in 24 Local US Health Departments: Best Practices and Lessons Learned

Abstract: IntroductionInstitutional mentoring may be a useful capacity-building model to support local health departments facing public health challenges. The New York City Department of Health and Mental Hygiene conducted a qualitative evaluation of an institutional mentoring program designed to increase capacity of health departments seeking to address chronic disease prevention. The mentoring program included 2 program models, a one-to-one model and a collaborative model, developed and implemented for 24 Communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Generic materials can have impact in fostering organizational change when users can also tailor them to their own situations (Veatch, Goldstein, Sacks, Lent, & Van Wye, 2014). The developers determined to find ways for stakeholders to customize the resource to make it as effective as possible.…”
Section: The Action Guide Designmentioning
confidence: 99%
“…Generic materials can have impact in fostering organizational change when users can also tailor them to their own situations (Veatch, Goldstein, Sacks, Lent, & Van Wye, 2014). The developers determined to find ways for stakeholders to customize the resource to make it as effective as possible.…”
Section: The Action Guide Designmentioning
confidence: 99%
“…However, not many interventions have looked at using a collaborative partnership to establish workplace lactation support. One study reported using an institutional mentor-mentee approach to assist local health departments in addressing obesity, tobacco use, and breastfeeding in the hospital setting (Veatch, Goldstein, Sacks, Lent, & Van Wye, 2014). This study revealed that mentees who worked with an institutional mentor improved their ability to achieve their lactation objectives.…”
Section: Introductionmentioning
confidence: 99%